Endoscopic spray cryotherapy for dysphagia palliation in esophageal cancer: Systematic review and meta-analysis - Gopakumar, Harishankar; Khan, Hamza; Sharma, Neil; Puli, Srinivas Reddy (Endoscopy International Open, 2024)
Background and study aims Endoscopically delivered liquid nitrogen spray cryotherapy is reported to be a safe and possibly more effective strategy for dysphagia palliation in patients with advanced esophageal cancer. This systematic review and meta-analysis aimed to pool all available data to evaluate the impact of this treatment modality.Methods Electronic databases (PubMed, Embase, and Cochrane Library) from January 2005 through June 2023 were searched for studies evaluating endoscopically delivered liquid nitrogen spray cryotherapy for dysphagia palliation in patients with advanced esophageal cancer. Pooled proportions were calculated using random-effects (DerSimonian-Laird) model.Results From an initial 895 studies, data were extracted and analyzed from five studies comprising a total of 230 patients that met inclusion criteria. In this pooled analysis, dysphagia improved or did not deteriorate in 81.40% of patients (95% confidence interval [CI] 73.75–87.99). Significant improvement in dysphagia was reported by 55.19% of patients (95% CI 29.62–79.37). An alternate method of dysphagia palliation despite spray cryotherapy was required in 18.78% of patients (95% CI 8.09–32.63) with 10.56% (95% CI 2.53–23.18) requiring esophageal stents. The weighted mean number of spray cryotherapy sessions per patient was 3.37 (95% CI 2.55–4.18). The pooled major adverse event rate was 3.26% (95% CI 0.15–10.14).Conclusions Endoscopic liquid nitrogen spray cryotherapy can effectively and safely treat dysphagia in esophageal cancer. It can be considered an option for dysphagia palliation in centers with expertise and equipment.
Keywords: Barrett's and adenocarcinoma; Malignant strictures; RFA and ablative methods; Endoscopic ultrasonography; Esophageal cancer